Prevalence of Adult Celiac Disease in India: Regional Variations and Associations. (January 2016) - Ramakrishna, B S; Makharia, Govind K; Chetri, Kamal; Dutta, Sangitanjan; Mathur, Prashant; Ahuja, Vineet; Amarchand, Ritvik; Balamurugan, Ramadass; Chowdhury, Sudipta D; Daniel, Dolly; Das, Anup; George, Gemlyn; et al.
Abstract : Objectives: Although celiac disease (CeD) affects 1% of people in the northern part of India, it is believed to be uncommon in the southern and northeastern parts because of significant differences in dietary pattern and ethnicity. We estimated the prevalence of CeD in these three populations. In a subset, we also investigated differences in the prevalence of HLA‐DQ 2/8 allelotype and dietary grain consumption. Methods: A total of 23, 331 healthy adults were sampled from three regions of India—northern ( n =6207), northeastern ( n =8149), and southern ( n =8973)—and screened for CeD using IgA anti‐tissue transglutaminase antibody. Positive tests were reconfirmed using a second ELISA. CeD was diagnosed if the second test was positive and these participants were further investigated. A subsample of participants was tested for HLA‐DQ2/‐DQ8 and underwent detailed dietary evaluation. Results: Age‐adjusted prevalence of celiac autoantibodies was 1.23% in northern, 0.87% in northeastern, and 0.10% in southern India ( P <0.0001). Prevalence of CeD and latent CeD, respectively, was 8.53/1, 000 and 3.70/1, 000 in northern, 4.66/1, 000 and 3.92/1, 000 in northeastern, and 0.11/1, 000 and 1.22/1, 000 in the southern part. The population prevalence of genes determining HLA‐DQ2 and/or ‐DQ8 expression was 38.1% in northern, 31.4% in northeastern, and 36.4% in southern India. Mean daily wheat intake was highest in northern (455 g) compared with northeastern (37 g) or southern part (25 g), whereas daily rice intake showed an inverse pattern. Conclusions: CeD and latent CeD were most prevalent in northern India and were the least in southern India. The prevalence correlated with wheat intake and did not reflect differences in the genetic background.